Dietary knowledge, Attitude and Practices of Diabetes Patients at Services Hospital Lahore - Bano, Anbreen; Afzal, Muhammad; Sarwar, Hajra; Waqas, Ali; Kousar, Samina; Gulzar, Saima (International Journal of Applied Sciences and Biotechnology, 2017)
Introduction: Diabetes mellitus is growing fastly the world is witnessing. The incidence of alarming concern to health care providers is rapidly rising. The main burden of this disease will fall on all developing countries. The number of diabetic patients will reach 300 million by the end of 2025 it is known through the estimation mostly developing countries will have such a dramatic and significant impacts. Methodology: The quantitative descriptive cross-sectional study design was used with convenient sampling (n=142) from Services Hospital Lahore. Using the questioner consist of 34 items data was analyzed through spss21 version descriptive analyses and the chi-square test with (p=<0.05) was used. Results: Findings of the study that only 19% had good knowledge they answered 8 or more correct responses remaining 81% participants answered less than 50% correct responses had poor knowledge. The 41.5% had positive attitude with diabetic diet while the remaining 58.5% were having negative attitude. The findings also revealed that only 17.6% had good practices they answered 50% and above correct responses while the others 82.4% participants answered less than 50% correct responses and were doing poor practices about the diabetic diet. The significant association was found between the gender and patient’s knowledge and no significant association between the education and patient’s dietary knowledge. Conclusion: The diabetes type 2 patients should have up to mark dietary, knowledge, and keep it in practicing well. It will, prevent from diabetes complications. There is need to improve the patients knowledge and provide education them. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 227-236